STRATEGI PEMASARAN DODOL NANGKA PADA UD. WARNA SARI DI DESA SURANADI KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - I GUSTI AGUNG DIDIT EKA PERMADI; NI NYOMAN HARNIKA (GANEC SWARA, 2021)
UD. Warna Sari is agroindustry of various kinds of food, namely jackfruit lunkhead, soursop lunkhead, pineapple dodol, sticky rice lunkhead, banana chips, sweet potato chips, and others. The purpose of this study is to analyze the marketing strategy of jackfruit dodol at UD. Warna Sari in Suranadi Village, Narmada District, West Lombok Regency. This research is a descriptive study. The data analysis tool used in this study is the SWOT analysis (Strength, Weakness, Opportunity, and Threats). Based on the results of the SWOT analysis, it can be concluded that the Internal Strategic Factor Analysis Summary (IFAS) has a value of -1.692 while the External Strategic Factor Analysis Summary (EFAS) is 0.04 so that it forms a cartesian coordinate point in Quadrant III (Turn Around Strategy). It can be concluded that the right strategy to be implemented by UD. Warna Sari in Suranadi Village, Narmada District, West Lombok Regency, namely the WO (Weaknesses-Opportunities) Strategy